Utility of NT-proBNP as a rule-out test for left ventricular dysfunction in very old people with limiting dyspnoea: the Newcastle 85+ Study - Collerton, Joanna (BioMed Central, 2014)
BACKGROUND: Guidelines advocate using B-type natriuretic peptides in the diagnostic work-up of suspected heart failure (HF). Their main role is to limit echocardiography rates by ruling out HF/LV dysfunction where peptide level is low. Recommended rule-out cut points vary between guidelines. The utility of B-type natriuretic peptides in the very old (85+) requires further investigation, with optimal cut points yet to be established. We examined NT-proBNP's utility, alone and in combination with history of myocardial infarction (MI), as a rule-out test for LV dysfunction in very old people with limiting dyspnoea. METHODS: Design: Cross-sectional analysis. Setting: Population-based sample; North-East England. Participants: 155 people (aged 87-89) with limiting dyspnoea. Measures: Dyspnoea assessed by questionnaire. Domiciliary echocardiography performed; LV systolic/diastolic function graded. NT-proBNP measured (Roche Diagnostics). Receiver operating characteristic analyses examined NT-proBNP's diagnostic accuracy for LV dysfunction. RESULTS: AUC for LVEF less than or equal to 50% was poor (0.58, 95% CI 0.49-0.65), but good for LVEF less than or equal to 40% (0.80, 95% CI 0.73-0.86). At ESC cut point (125ng/l), few cases of systolic dysfunction were missed (NPV 94-100%, depending on severity), but echocardiography (88%) and false positive rates (56-81 per 100 screened) were high. At NICE cut point (400ng/l), echocardiography (51%) and false positive rates (33-45) were lower; exclusionary performance was good for LVEF less than or equal to 40% (1 case missed per 100 screened, 15% of cases; NPV 97%), but poor for LVEF less than or equal to 50% (16 cases missed per 100 screened, 45% of cases; NPV 68%). Incorporating isolated moderate/severe diastolic dysfunction into target condition increased the proportion of cases missed (lower NPV), whilst improving case detection. Incorporating MI history as an additional referral prompt slightly reduced the number of cases missed at expense of higher echocardiography and false positive rates. CONCLUSIONS: High echocardiography rates and poor exclusionary performance for mild degrees of systolic dysfunction and for diastolic dysfunction limit NT-proBNP's utility as a rule-out test for LV dysfunction in very old people with limiting dyspnoea. Incorporating MI history as an additional echocardiography prompt yields no overall benefit compared to using NT-proBNP level alone. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2261-14-128) contains supplementary material, which is available to authorized users.